Do the Big Five personality traits predict individual differences in the left cheek bias for emotion perception?. Issue 3 (3rd May 2016) - Galea, Samantha; Lindell, Annukka K.
ABSTRACT: Like language, emotion is a lateralized function. Because the right hemisphere typically dominates emotion processing, people express stronger emotion on the left side of their face. This prompts a left cheek bias: we offer the left cheek to express emotion and rate left cheek portraits more emotionally expressive than right cheek portraits. Though the majority of the population show this left cheek bias (60–70%), individual differences exist but remain largely unexplained. Given that people with higher self-rated emotional expressivity show a stronger left cheek bias, personality variables associated with increased emotional expressivity and emotional intelligence, such as extraversion and openness, may help account for individual differences. The present study thus examined whether the Big Five traits predict left cheek preferences. Participants ( M = 58, F = 116) completed the NEO-Five Factor Personality Inventory (NEO-FFI) [Costa, P. T. J., & McCrae, R. R. (1992). NEO PI-R professional manual . Odessa, FL: Psychological Assessment Resources] and viewed pairs of left and right cheek images (half mirror-reversed); participants made forced-choice decisions, indicating which image in each pair looked happier. Hierarchical regression indicated that neither trait extraversion nor openness predicted left cheek selections, with NEO-FFI personality subscales accounting for negligible variance in preferences. As the Big Five traits have been discounted, exploration of other potential contributors to individual differences in the left cheek bias is clearly needed.